NHC-catalyzed [4 + 2] annulations of allenoates and 2, 3-dioxopyrrolidine derivatives. Issue 6 (18th January 2022) - Song, Xue; Chen, Yangxu; Lu, Fangfang; Zhang, Kai; Yu, Chenxia; Li, Tuanjie; Yao, Changsheng
Abstract : A facile NHC-catalyzed [2+4] annulation of allenoates with 2, 3-dioxypyrrolidine derivatives was discovered, which paved a new avenue to the construction of highly substituted pyranopyrrole with moderate to good yields. Abstract : A facile NHC-catalyzed [2 + 4] annulation of allenoates with 2, 3-dioxypyrrolidine derivatives was discovered, which paved a new avenue for the construction of highly substituted pyranopyrrole with moderate to good yields, high atom economy and mild reaction conditions.